The Aura of the Object and the Work of Art: A Critical Analysis of Walter Benjamin’s Theory in the Context of Contemporary Art and Culture - Vassilev, Kiril (Arts (Basel), 2023)
This text is a critical interpretation of Walter Benjamin’s theory in the context of the contemporary situation in art and culture. Benjamin’s innovative method of analysis and key concepts in art theory and their simultaneous research and political function are carefully reconstructed. This critical analysis is centered on the main concept of Benjamin’s philosophical aesthetics, the concept of ‘aura’. This analysis shows how Benjamin mixes and replaces the aura of the work of art with the aura of the historical object. Benjamin’s main thesis about the loss of the aura of the work of art in the age of its technical reproducibility is disputed. Technical reproducibility does not take away the aura of the work of art, but separates its aura from the aura of the historical object. Auraticness is inherent in every work insofar as it is a work of art. The aura of the historical object does not disappear in modernity either. With the emergence of historical and aesthetic consciousness, of the historical and art museum, the almost mechanical production of auratic objects began in modernity. As a result of the critical analysis of the concept of “aura”, the main binary oppositions that frame Benjamin’s theory of art—art with aura/art without aura; art with cult value/art without cult value; aestheticization of politics/politicization of art—are questioned. At the end of this text, the key lines of analysis proposed by Benjamin in an attempt to make sense of the radical changes in art since the beginning of the 20th century are used to outline the contemporary situation in art and the changes in perception with which it is associated.